PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 169 PEKANBARU - Elita Fitri Yana Fitri Yana; Gustimal Witri Gustimal Witri; Erlisnawati Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problem in this research was social studies students achievement in fourth graderes (IV) SDN 169 Pekanbaru still low with average value 64,16 (with KKM 75). The purpose of this research was to improve the students achievement of the fourth graderes (IV) SDN 169 Pekanbaru. with the implementation of Problem Based Learning model. This research was an classroom action research with two cycles in second semester 2014/2015. Before implementation Problem Based Learning modelaverage 64,16,after implementation of Problem Based Learning model, UH I was 73,37 that improve 14,35% from before exam with average 64,16. UH II was85,23 that improve 32,83%. Teacher’s activities with the implementation of Problem Based Learning model at first meeting of first cycle was 65% (good category), and second meeting was 70% (good category) that improve 5 point. At second cycle, theacher’s activitiesat first meeting was 85% (good category) that improve 15 point from second meeting of first cycle. Second meeting of second cycle was 90% (verygood category) which improve 5 point. Students activitesat first meeting of first cycle was 60% (enough category), and second meeting 75% (good category) that improve 15 point. At second cycle, students activities at first meeting was 85% (good category) that improve 10 point from second meeting of first cycle. Second meeting of second cycle was 90% (verygood category) which improve 5 point. Implementation of Problem Based Learning modelcan improved social studies students achievement of fourth graderes (IV) SDN 169 Pekanbaru.Key Words: Problems Basd Learning, Sosial Studies Student’s Achievement